Pola Motivasi Intrinsik Kreator Konten Dalam Menggunakan Bahasa Inggris Pada Media Sosial - Vijaya, Rosyidah Jayanti; Nurharjanti, Marita; Hesvindrati, Netci (P3M Politeknik Negeri Media Kreatif, 2025)
Intrinsic motivation plays a role in the creators' decision to use English. The urgency of this research arised because some content creators were unaware of the intrinsic motivations that drive them to use English when delivering messages. This quantiative study aims to identify content creators’ four dimensions of intrinsic motivation (interest/enjoyment, perceived ability, effort, and pressure) in using English Data collection was conducted through a closed questions questionnaire disseminated to 32 creators who were scrapped from AllSyars website, used English in some of their postings, and had >50% engagement rate. The descriptive analyses results show content creators’ intrinsic motivation in using English in conveying their messages. The results also indicate the average value of the intrinsic motivation during the content making process. The findings are expected to raise content creators’ self-awareness of intrinsic motivation and help them build and nurture their personal branding on social media.